Nanophthalmos: An Update on the Biological Parameters and Fundus Abnormalities. (11th March 2021) - Yang, Ning; Zhao, Liang-Liang; Liu, Jia; Ma, Lin-Lin; Zhao, Jin-Song
Abstract : Nanophthalmos is a clinical phenotype of simple microphthalmos, in which the anterior and posterior segments of the eyeball do not develop into a normal size without other major ocular or systemic anomalies. Typical clinical manifestations of nanophthalmos include short axial length, thickened sclera, small cornea, shallow anterior chamber, and increased lens-to-eye volume ratio. Currently, there is a lack of recognized diagnostic criteria for nanophthalmos. With the development of eye examination technologies, such as biological measurement and imaging examination, visualization and quantification of the eyeball's shape and structure in nanophthalmos can be realized. New clinical features have been reported, which are of great significance for diagnosing and treating nanophthalmos. This review introduces the related concepts of nanophthalmos and the new developments in its clinical characterization.